Food processing of horticultural crops - Gautam, Harender Raj and Sharma, H.L. (Kurukshetra: A Rural Development Monthly Since 1952)
Food processing has a critical role in achieving food and nutrition society. It is required to increase the shelf life of foods and is of almost importance for perishable commodities like fruits and vegetables to optimize nutrient availability and food quality and reduce losses and waste. India is the sixth largest food and grocery market in the world and food processing industry contributes 32% to this food market.- Reproduced